Race-Based Trauma in Counselor Education: A Proposed Antiracist-Humanistic Course Curriculum - White Jr, Dwayne Maurice; Jarrett, Jodi; Green, Darius A.; Evans, Amanda M. (ILIN Education Indonesia, 2025)
The synonymic nature of humanistic scholarship suggests that to be a clinician with a humanistic focus, one must be an antiracist. Many practicing counselors report not receiving training on identifying and treating race-based trauma. This study, presented as a conceptual analysis, draws on secondary data sources including scholarly journals, textbooks, and online materials to propose a race-based trauma course curriculum. Methods of curriculum design include reviewing existing research, identifying critical gaps in multicultural training, and structuring content around self-awareness, knowledge, skill development, and advocacy. The discussion highlights the need for counselor educators to integrate antiracist-humanistic strategies to better prepare students for addressing race-based trauma in clinical practice. This work concludes with implications for counselor education programs to strengthen responsiveness to address training students in race-based trauma.